Incidence of Oral Communication Problems in Patients at KATH, Ghana (Journal of Science and Technology, 2016)
The data of 623 patients who reported for the management of oral disorder at the Komfo Anokye Teaching Hospital (KATH) in Kumasi, Ghana within a period of four years were retrospectively analysed and studied in result of differences in the type of problems, age group, sex and geographical location.Oral communication disorder affects all age groups and had high incidence in young children, infants and males. Decoding – encoding difficulty was prevalent by encoding difficulty, faulty encoding and loss of ability to decode or encode speech. Majority of the patients came from the Ashanti Region followed by stations around Kumasi, areas in Kumasi central and finally, other regions of Ghana.  The results are discussed.